If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -1x = 34 + -3x Solving 26 + -1x = 34 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 26 + -1x + 3x = 34 + -3x + 3x Combine like terms: -1x + 3x = 2x 26 + 2x = 34 + -3x + 3x Combine like terms: -3x + 3x = 0 26 + 2x = 34 + 0 26 + 2x = 34 Add '-26' to each side of the equation. 26 + -26 + 2x = 34 + -26 Combine like terms: 26 + -26 = 0 0 + 2x = 34 + -26 2x = 34 + -26 Combine like terms: 34 + -26 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 1/25=y/1250 | | 2u-2.3=4.1 | | 2(x+2)-8=12 | | 8/3=t/12 | | 5n^2+8=0 | | -7y+22.9=5.4 | | 14p-21q= | | 7x+9=6x+-5 | | 9x(7+8)= | | 5m^2+5m-30=0 | | 2x+4y+5z=8 | | 3x-6.2=3.4 | | [x-2]=14 | | 104.2+82.3+x=151.3 | | 1-4x/3=3 | | -12x^2+x+11=0 | | 16/(8x-20) | | (5x-25)/(5x-5) | | 19+4x+3x=124 | | 9-3x/9=-11 | | 3(v-2)=9v+3-5(-2v-1) | | 7x+10y=263 | | 4(5x+1)=3-(5x-5) | | 6a+5whena=8 | | x^3-3x^2-49x-147=0 | | 4(9-x)=-8 | | 7+3(2w-1)=-2(8w-9)+6w | | 12r+15=155-2r | | 3c-5=14c-27 | | 50-n=35 | | x^2-3x+438=0 | | 10v+14=80-v |